Obestasis - Sanjay Kalra; Sourabh Sharma; Saurabh Arora; Nitin Kapoor (Journal of the Pakistan Medical Association, 2025)
Obestasis, a commonly experienced phenomenon, is the term given to the mild, pitting oedema that is associated with obesity. Obestasis can be due to various disorders, including lymphatic, microcirculatory and venous dysfunction, as well as sarcopenia. It can be worsened by protein deficiency, excessive salt intake, poor physical conditioning, and tight clothing or foot wear. Obestasis can also be iatrogenic, and can be a part of premenstrual syndrome. Obestasis may lead to variation in body weight, and impair quality of life. The management of obestasis is multifactorial, and includes nutritional optimization, lifestyle modification, rational pharmacological therapy and reassurance. Keywords: Drug-induced oedema, iatrogenic, oedema, overweight, weight gain.